Association of The Healthy Eating Index and Body Composition Among Iran’s Paralympic Athletes with Hemodialysis and Hemophilia - Easa Murad AL-Rubaye , Thaer (Diyala Journal of Medicine, 2022)
Background: Essential parameters of athletes that enhancing their fitness and success rate in sports career are body composition and anthropometric indices, additionally perfect performance of athletes with a prolonged and intensive season is significantly influenced by dietary intake and training. Objective: To determine the association between the healthy eating index (HEI) and body composition among Iran’s Paralympic athletes with hemodialysis and hemophilia. Patients and Methods: A study with a cross-sectional design was carried out, which recruited 100 athletes with hemodialysis and hemophilia who participated in the 2020 competitive pre-season tests. Sociodemographic, anthropometric, physical activity, sleep pattern, and dietary intake were used in the analysis. The quality of the diet was assessed using the HEI score, with a range of 0 to 100, based on information obtained using food frequency questionnaire. Body components parameters were assessed using Bio impedance analyzer BIA (TANITA BC- 418 (TANITA, Japan) and 7-points skinfold measures, linear regression model was used for finding the associations between HEI and body composition. Results: The overall HEI score was 67.81 (grade D) and there was a significant difference for the mean body fat percent (P=0.001) and mean fat free mass percent (P=≤0.001) between 7-points skinfold measurements and BIA. No significant association had been found between the resulting HEI of the participants with the components of their body composition including, body mass index BMI (P=0.57), waist circumference WC (P=0.53), waist hip ratio WHR (P=0.18), fat percent (P=0.76) and fat free mass percent (P=0.76). Conclusion: It can be concluded that the dietary intake need more improvement, we did not find any significant associations between HEI (diet quality) with the parameters of body composition